2019
DOI: 10.3390/rs11202421
|View full text |Cite
|
Sign up to set email alerts
|

Greening Implication Inferred from Vegetation Dynamics Interacted with Climate Change and Human Activities over the Southeast Qinghai–Tibet Plateau

Abstract: Vegetation dynamics are sensitive to climate change and human activities, as vegetation interacts with the hydrosphere, atmosphere, and biosphere. The Yarlung Zangbo River (YZR) basin, with the vulnerable ecological environment, has experienced a series of natural disasters since the new millennium. Therefore, in this study, the vegetation dynamic variations and their associated responses to environmental changes in the YZR basin were investigated based on Normalized Difference Vegetation Index (NDVI) and Glob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 96 publications
0
20
0
Order By: Relevance
“…The impact of urbanization on regional climate is due to variations in atmospheric thermal, dynamic and chemical components [6,7]. The formation of urban rainfall is dominated by urban heat island, changes in surface roughness and aerosol emissions coupled with regional topography and climate features [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The impact of urbanization on regional climate is due to variations in atmospheric thermal, dynamic and chemical components [6,7]. The formation of urban rainfall is dominated by urban heat island, changes in surface roughness and aerosol emissions coupled with regional topography and climate features [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies, increases in vegetation would positively contribute to increases in ET , which ultimately results in a negative contribution to runoff. Some studies have indicated that the vegetation in the entire YZRB has improved in recent decades, whereas the improvement of vegetation in the middle region was relatively significant, and variations of vegetation in the upper and lower regions were slight (Li et al, 2019; Liu, Niu, et al, 2019). In the upper region, the decreasing rate of P and the increasing rate of R t was −0.72 and 0.11 mm per year respectively, which were both statistically non‐significant ( |Z c | < 1.96).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, 1997 was identified as the runoff breakpoint and was chosen as the datum point representing the baseline vegetation period (period I), and the GIMMS‐NDVI3g dataset from 1997 to 2015 was used to analyse the variations in vegetation during the change period (period II) compared to the baseline period (period I) in the upper, middle, and lower regions. An NDVI variation trend analysis coupled with a significance test was implemented according to the method proposed by Li et al (2019), and the categorized criteria of the NDVI trend are shown in Table 6. The spatial distribution of the NDVI variation trend is shown in Figure 6.…”
Section: Resultsmentioning
confidence: 99%
“…Even though a general greening trend was reported in the context of climate warming for many mountain ranges in the European Alps [46,127], North America [113], High Mountain Asia [128,129] and Arctic and sub-Arctic environments [130,131], some studies found transforming forces on cold-adapted plant communities and reduction of vegetation cover, most probably related to a climate-induced temperature rise and concomitant drier conditions [129,132,133]. Drought effects can probably be precluded in our study area at least for the study year 2019, as the water potential measurements have shown more than −1.6 MPa moisture (data not shown) and thus, according to Körner [134], sufficient water availability for plants was ensured.…”
Section: Trends Of Temperature Glacier Retreat and Vegetation Covermentioning
confidence: 99%